Shear strength of post-installed connectors in thin UHPC precast walls. (February 2023) - Prejs, Andy; Jawdhari, Akram; Fam, Amir
Abstract: Ultra-high-performance concrete (UHPC) is seeing increased application in the precast industry, as in insulated double wythe precast concrete (DWPC) panels for examples, where very thin profiles can be produced. This pauses a challenge with regard to connections, where conventional headed studs are not suitable. This paper presents an experimental campaign of 143 shear strength tests investigating the behavior of screw anchors and a newly designed threaded rod connector embedded in thin UHPC members. Parameters examined were slab thickness ( tc ), connector diameter ( d ), fiber percentage ( pf ) in UHPC, edge distance ( c1 ), and support span length ( ls ). All specimens failed in shear concrete breakout with instances of splitting cracks, varying failure cone angles, and spalling. The threaded rod demonstrated better structural performance with ultimate shear loads ( Vu ) 29–93 % greater than the screw anchor. Increasing c1 had the most significant effect on Vu, where it was over two times greater when c1 was increased from 38 to 89 mm. Increasing tc from 25 to 38 mm resulted in Vu increasing by 24–43 % for the screw anchor. Meanwhile for the threaded rod, Vu increased by 1.3–3.3 times when tc increased from 15 to 25 mm. Results showed that d, pf, and ls did not have significant effect on Vu . Two existing models were evaluated and were found to overestimate the shear capacity of the connectors. A regression analysis was performed on the data and two design equations were developed to predict the shear capacity of each connector with a high degree of accuracy. A design case study is also presented.